Aggregate Stability and Soil Moisture Improvement As Affected By Bokashi Application and Soil Tillages for Cabbage (Brassica oleraceae L) Cultivation on Ultisol - Desfar Tamara Eka Putra; M. Faiz Barchia; Kanang Setyo Hindarto; Bilman W. Simanihuruk; Herry Gusmara; Widodo Widodo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
The aims of this study were 1) to find optimum dose of bokashi applied for cabbage growth based on the improvement of the total soil aggregate stability, soil moisture content, soil pH, 2) to find soil tillage method for optimum growth of cabbage based on the improvement of the total soil aggregate stability, soil moisture content, soil pH, , and (3) to find interaction between dose of bokashi applied and soil tillage method for the optimum growth of cabbage. This research was conducted from March to June, 2020 in Muara Bangkahulu sub-district, Bengkulu City. The research location lies on ± 500 m above sea level with soil type of Ultisol. The research used Split plot design with 3 replications. The main plot was 3 soil tillage methods involved no tillage, minimum tillage (1 time hoe tillage), and intensive tillage (2 time hoe with 1 time rake), and the sub plot consist of 4 doses of bokashi involved 0 ton ha-1, 5 tons ha-1, (2,81 kg plot-1), 10 tons ha-1, (3,75 kg plot-1), and 15 tons ha-1 (5,62 kg plot-1). The research resulted there was interaction between the soil tillage method and the bokashi applied on the improvement on the total soil aggregate stability. An increasing dose of bokashi applied on all soil tillage treatments was followed by the increasing the total soil aggregate stability. Minimum- and intensive soil tillage methods gave better growth of cabbage in form of the plant height and the leaf number than no tillage to the cabbage growth. Bokashi applied with doses of 10 tons ha-1 and 15 tons ha-1 improved soil pH, soil moisture content, and the cabbage growth.